(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the prevalence of erectile dysfunction and anxiety among male patients with type 2 diabetes mellitus, and to evaluate the relationship between these two disorders. Method: A cross-sectional descriptive study was conducted on 78 male type 2 diabetes mellitus patients with erectile dysfunction at Bach Mai Hospital from August 2024 to August 2025. Erectile dysfunction was evaluated using the IIEF-5 and anxiety using the GAD-7. Data were analyzed using SPSS 20.0. Results: The mean age of participants was 53.26 ± 9.05 years. The rates of mild, mild-moderate, moderate, and severe erectile dysfunction were 41%, 32.1%, 16.7%, and 10.3%, respectively. Anxiety was present in 78.21% of cases (41% mild, 35.9% moderate, and 14.1% severe). A significant negative correlation was observed between IIEF-5 and GAD-7 scores (r = -0.645, p < 0.001). Conclusion: Both erectile dysfunction and anxiety are common in male type 2 diabetes mellitus patients, and they are closely associated. Early screening and intervention are essential to improve quality of life.